La motivación lingüística de algunos nombres que designan entidades de tiempo en español - Brzozowska-Zburzyńska, Beata (Studia Romanica Posnaniensia, 2025)
In cognitive linguistics, the idea that words are not totally arbitrary is accepted, contrary to what de Saussure stated in his Theory of the Linguistic Sign. When analyzing them, from the etymological and historical point of view, different linguistic motivations can be found that cause a word to have this or that meaning. The interesting thing is that these motivations are not identical if we compare different languages and even within the framework of the same language we can find different motivation for synonymous terms or we can indicate others by comparing some dialectal or social variants of the same language. The purpose of this study is to present and analyze the motivation of the terms that name different temporal entities. Thus, for example, what is the motivation for the word puente that designates a period of non-working days and what its variants can be in non-peninsular Spanish. To carry out the study we will use the tools of cognitive semantics and more especially the concepts that come from the Theory of Cognitive Metaphor and Metonymy.